Efficacy of Chinese Herbal Formula Sini Zuojin Decoction in Treating Gastroesophageal Reflux Disease: Clinical Evidence and Potential Mechanisms - Li, Shaowei; Huang, Mengfen; Wu, Guojing; Huang, Weihan; Huang, Zhanhui; Yang, Xiaoqian; Ou, Jinming; Wei, Qipeng; Liu, Chengli; Yu, Shaoyuan (Frontiers in Pharmacology, 2020)
Background: Based on 122 cases reporting in China, data mining indicated that Sini Powder (SNP) and Zuojin Pill (ZJP) are both widely used as the basic recipe of treating Gastroesophageal Reflux Disease (GERD). Objectives: To evaluate the intervention effects of Sini Zuojin Decoction (SNZJD) in patients with GERD. Methods: A comprehensive collection of randomized controlled trials (RCTs), which were published in domestic and foreign journals using SNZJD in patients with GERD, were collected by computer retrieval. RevMan5.3 software was used for meta-analysis and bias risk assessment, Stata14.0 software was used for sensitivity-analysis, GRADE profile 3.6 was used to evaluate the level of evidence, and trial sequential analysis (TSA), used to control for random errors, was performed to assess the main outcomes. Network pharmacology analysis was applied to preliminarily study the action mechanisms of SNZJD on GERD. Results: 13 articles were eventually included, with a total of 966 patients. Meta-analysis indicated that: ① SNZJD plus traditional stomach medicines (SPTSM) group was more effective than traditional stomach medicines (TSM) group (RR = 1.16, 95 % CI [1.04, 1.29], P = 0.009); ② Experimental group with SNZJD was significantly better than TSM controls in improving heartburn, substernal chest pain, acid regurgitation and food regurgitation symptoms (P < 0.0001); ③ SPTSM could significantly decrease total symptom scores with an important effectiveness (P ＜ 0.00001). The recurrence rate and adverse effects of SNZJD treatment were significantly reduced (P ＜ 0.05). TSA showed that the effective rate of Meta-analysis might be reliable, but the recurrence and safety results were still uncertain. According to the evaluation of the GRADE method, the quality of evidence was low-level. Besides, SNZJD might treat GERD by acting on related targets and pathways such as inflammation, hormone regulation and so on. Conclusions: SNZJD might be useful in the treatment of GERD, but its long-term effects and specific clinical mechanisms were unclear. Due to the poor quality of the evidence, more samples and high-quality clinical studies should be tested and verified in the future.